1997
DOI: 10.1021/jm970216k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of a New Model of Arylpiperazines. 3. 2-[ω-(4-Arylpiperazin-1-yl)alkyl]perhydropyrrolo- [1,2-c]imidazoles and -perhydroimidazo[1,5-a]pyridines:  Study of the Influence of the Terminal Amide Fragment on 5-HT1A Affinity/Selectivity

Abstract: A series of new arylpiperazine derivatives 2, which are devoid of the terminal amide fragment present in related 5-HT1A ligands, was prepared and evaluated for affinity at 5-HT1A and alpha 1 receptors. All the compounds 2 demonstrated high affinity for the 5-HT1A receptor and moderate affinity for alpha 1 receptor binding sites. Structure-activity relationship (SAR) studies suggest that there is influence of electronic factors on the no-pharmacophoric part of the alpha 1 receptor site. However there is no infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…At the same time it is clear that high affinity ligands should have a long enough linker chain with at least four methylene groups. These findings correspond to pharmacophore modeling and experimentally observed relationships. Of course, both models PLS and RF have some discrepancies in calculated contribution values, since different interpretation approaches were used and the modeling property is not additive. However, that did not interfere with retrieving similar structure–activity relationship trends and correct conclusions.…”
Section: Visualization Of Descriptor Contributionssupporting
confidence: 81%
“…At the same time it is clear that high affinity ligands should have a long enough linker chain with at least four methylene groups. These findings correspond to pharmacophore modeling and experimentally observed relationships. Of course, both models PLS and RF have some discrepancies in calculated contribution values, since different interpretation approaches were used and the modeling property is not additive. However, that did not interfere with retrieving similar structure–activity relationship trends and correct conclusions.…”
Section: Visualization Of Descriptor Contributionssupporting
confidence: 81%
“…In order to have a better understanding of the influence of the electronic properties of the terminal amide fragment on the affinity toward α 1 -AR, the isosteric change of a carbonyl into a methylene group was investigated (compounds 17 in Fig. (2)) [24]. As a result, the general trend showed a marked drop in affinity (16a versus 17a, and 16b versus 17b, Table 2).…”
Section: Sar On the Spacer Linking The Terminal Fragment To The Pipermentioning
confidence: 99%
“…In addition, further simplification of the heteroring, such as reduction in the number of nitrogen atoms, afforded compounds with enhanced activity, being unsubstituted 1-benzimidazole and 1-indole derivatives the most active compounds of these series [27]. On the other hand, when the carbonyls of a hydantoin moiety were isosterically substituted with methylene groups, a negative influence in the α 1 -AR affinity was found [24], in agreement with the pharmacophore model suggestions indicating the presence of a hydrogen bond acceptor group in the region of space occupied by the heteroring. 2) Considering the effect of substitution at the ortho, meta, and para position of the phenyl ring attached to the piperazine nucleus, the m-chloro group of trazodone was replaced by an o-chloro or o-methoxy substituent.…”
Section: Arylpiperazines Acting As α 1 -Ar Subtype Selective Antagonistsmentioning
confidence: 99%
“…Several early front-runners of pure antagonists are arylpiperazine derivatives such as NAN-190, which displays high affinity for 5-HT 1A receptors ( K i = 0.6 nM), but also has a high potency for the α 1 receptor. In addition, NAN-190 displays partial agonist-like activity in a radioligand binding assay. BMY7378 appears to exhibit the same partial agonist property , However, it was quickly surpassed by a similar compound, WAY100635, which displayed a higher binding affinity ( K d = 0.10 nM) and better selectivity , while exhibiting no partial agonist property. , Recently, newer versions of arylpiperazines as 5-HT 1A receptor ligands have been reported . To develop radioiodinated ligands for in vivo imaging of 5-HT 1A receptors, we have previously reported a series of new arylpiperazine benzamido derivatives, including the antagonist ligand, 31 , and the iodinated agonist ligand, 8-OH-PIPAT …”
Section: Introductionmentioning
confidence: 99%
“…20,21 Recently, newer versions of arylpiperazines as 5-HT 1A receptor ligands have been reported. 22 To develop radioiodinated ligands for in vivo imaging of 5-HT 1A receptors, we have previously reported a series of new arylpiperazine benzamido derivatives, including the antagonist ligand, 31, 23 and the iodinated agonist ligand, 8-OH-PIPAT. 24 Results of in vitro binding and adenylyl cyclase assays for 31 demonstrated that it is an excellent "pure" antagonist with high affinity (K d ) 0.36 nM) and selectivity for 5-HT 1A receptors.…”
Section: Introductionmentioning
confidence: 99%